Phosphate Amendments to Compost for Improving P Bio-Availability. Issue 2 (3rd April 2019) - Redel, Yonathan D.; Nkebiwe, Peteh M.; Schulz, Rudolf; Müller, Torsten
Abstract: This study was conducted to investigate changes in P-fractions, bio-available P (CAL-P), citric acid extractable P, acid phosphatase activity and microbial biomass C and N during incubation of mature biogenic compost (MBC), immature biogenic compost (IBC) or immature sheep manure compost (ISC) not amended with P or amended with rock phosphate (RP, 7.6% P) or triple-superphosphate (TSP, 19.5% P). Incubation was performed at 20 °C in darkness under aerobic conditions. Samples were collected for laboratory analysis at the start of incubation (D-0) and after one, six and 26 days during incubation (D-1, D-6, D-26). Addition of soluble P fertilizer (TSP) led to a threefold increase in all P fractions in comparison to compost without TSP; even a "priming effect" could be observed, promoting conversion of non-labile to labile P. Moreover, addition of TSP lowered biological activity, especially acid phosphatase activity (P-ase), due to already high concentrations of readily available P. In general, P fractions (bicarbonate extractable Pi (NaHCO3 -Pi ) and bicarbonate extractable Po (NaHCO3 -Po ) and sodium hydroxide extractable Po (NaOH-Po )) increased during incubation until day 6 at the expense of NaOH-Pi fraction, which decreased. Generally, RP-derived P showed little or no effect on P fractions during the entire incubation period and only led to slightly increased CAL-P and Citric-acid-P levels. Fertilizer effects on labile P fractions were most enhanced with ISC. IBC enhanced microbial growth and P-ase, thereby enhancing conversion of labile into moderate labile NaOH-Po .